2021
DOI: 10.1088/1755-1315/694/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of size and shape rice seed to early seedling vigor traits

Abstract: Rice crop improvement program for direct-seeded has been directed at identifying the quality of seeds with rapid uniform germination and biomass accumulation during the initial phase of seedling establishment. Seed and embryo size are thought as two critical factors in the emergence of faster and vigorous seedlings. For the reason, this study was purposed to evaluate the relationship between the size and shape of rice seed with embryo size and its effects on germination. This study was designed using rice seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
3
0
2
Order By: Relevance
“…Almost all of the seedling traits were signi cantly different for each seed group (Table IV & V). However, this was contradicted by (Fauzi et al 2021) for the germination percentage. This variation in seedling traits may attributed to the embryo area (Mohsen, 2011) along with the availability of more amounts of food reserves provided to the embryonic plant (Ellis, 1992).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Almost all of the seedling traits were signi cantly different for each seed group (Table IV & V). However, this was contradicted by (Fauzi et al 2021) for the germination percentage. This variation in seedling traits may attributed to the embryo area (Mohsen, 2011) along with the availability of more amounts of food reserves provided to the embryonic plant (Ellis, 1992).…”
Section: Resultsmentioning
confidence: 93%
“…In many studies it has found that larger seeds have tendency to produce more vigorous seedlings (Ambika et al 2014). A strong correlation between germination potential and seedling vigour is reported in wheat (Kaur and Srivastava 1982) rice (Fauzi et al 2021), sun ower (Gadewar et al 2015). In rice the differences among the genotypes has proven genetic control in the manifestation of seed and seedling vigour (Akram et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Energi yang digunakan untuk proses perkecambahan masih dapat dipenuhi oleh cadangan makanan benih walaupun benih tersebut berukuran kecil (Kartikasari, 1999). Hal ini didukung oleh penelitian Fauzi et al (2021), perbedaan ukuran dan bentuk benih padi tidak berpengaruh nyata pada indeks vigor, kecepatan tumbuh, daya berkecambah, panjang radikula, panjang plumula, rasio panjang radikula dan plumula.…”
Section: Viabilitas Dan Vigor Benihunclassified
“…A study on 31 rice genotypes by Akshitha et al[6] for seedling vigour traits revealed a significant genotypic variability for dry weight with highest heritability. Teng et al[7] and Fauzi et al[8] also reported that heavier seeds produced higher seedling dry weight with higher leaf area resulting in faster canopy and higher photosynthetic activity and thereby have greater potential to compete with weeds under DDSR.The highest plant height was recorded in the variety WGL 915 (122.99 cm) and the variety RNR 15435 (121.72 cm) was found on par, while lowest plant height was found in WGL 962 (85.45 cm). Similar variation in plant height under direct sowing was observed by Goyal et al[9] and *,** represent significance at 0.05 and 0.01 levels probability respectively…”
mentioning
confidence: 99%